Isolated Pericardial Effusion and Transient Abnormal Myelopoiesis in a Fetus with Down's Syndrome - Hirashima, Chikako; Eguchi, Yukari; Kohmura, Yasuhiro; Minakami, Hisanori; Sato, Ikuo (The Journal of obstetrics and gynaecology research, 2000)
Isolated pericardial effusion was detected in a fetus at 34 weeks of gestation. A male infant weighing 2,044 g was born by cesarean section because of a non‐assuring fetal heart rate pattern at 35 weeks of gestation. Transient leukocytosis (36,100/μl) with 49% blast cells was seen in this neonate. The infant's karyotype was 47, XY + 21. The pericardial effusion disappeared after treatment with prednisolone at a dose of 2 mg/kg/day. Hypothyroidism was subsequently found. Thus, the subject patient with Down's syndrome developed isolated pericardial effusion, transient abnormal myelopoiesis (TAM), and hypothyroidism. Because more than 20% of the infants with TAM and Down's syndrome develop acute nonlymphocytic leukemia in early childhood, he is being closely observed.